Illegible : a novel - Gandlevskiĭ, Sergeĭ (NIU series in Slavic, East European, and Eurasian studies., 2019)
"First English translation of a prose novel by an acclaimed Russian poet. Set in Moscow in the 1970's, the novel follows a group of bohemian poets in both first and third person narratives"--